Interactions of stock market turnover and exchange rate volatility as determinants of net FDI inflows into emerging economies: an African empirical analysis - Mokgosi, Ipeleng (My University, 2018)
Investment by multinational firms into emerging markets can simply be put down to the attraction to new markets and their attractive operating environments. The cost of operation and ultimate profit will depend on the exchange rate between home country and foreign country. This study analyses the effects that African country exchange rate volatility and its’ interactions with stock market activity against G-7 nations has on the net foreign direct investment inflows into Africa. GARCH (1, 1), VAR and VECM methods were used for estimation of the results in this study. The findings are that stock market activity does drive the volatility of the exchange rate over an annual basis in some cases. Additionally, the exchange rate volatility is simply not a causal influence on whether more investment money flows into and African country versus flowing out
A research report submitted to the School of Economic and Business Sciences , n partial fulfilment of the requirements for the degree of Masters in Economics Research Report, 2018
Keywords: Financial services industry; Investments, Foreign--South Africa; Africa--Economic conditions